Audio Postproduction for Digital Video - Rose, Jay (Focal Press, 2012)
Written in the author's clear conversational style, with ample illustrations and visual analogies, this book features software agnostic tutorials and "cookbook recipes" for each phase of postaudio processing. The author begins with a section of FAQs from readers of the author's magazine column. After summarizing the significant points of audio theory, the author describes the preliminaries of setting up a post studio. From there he details every aspect of postproduction - from getting the tracks into the computer, to 'fixing and mixing, ' to dealing with details of compression and streaming. The companion audio CD contains diagnostics, tutorial tracks, and demonstrations.